Show me the magic - Mazursky, Paul (1999)
Paul Mazursky--writer, film director, actor, and producer--has created a body of work over the past thirty years that has established him as one of America's most respected and admired filmmakers. His films are often personal, intimate, and humorous observations of the human condition.